Development and validation of a LAMP-based method for rapid and reliable detection of Xanthomonas albilineans, the causal agent of sugarcane leaf scald - Chakraborty, Moutoshi; Bhuiyan, Shamsul Arafin; Strachan, Simon; Shiddiky, Muhammad J. A.; Nguyen, Nam-Trung; Ford, Rebecca (Frontiers in Microbiology, 2025)
IntroductionXanthomonas albilineans (Xalb)-induced leaf scald (LS) is a significant bacterial disease affecting sugarcane and posing a global threat to the sugarcane industry. The presence of irregular symptoms makes traditional phenotypic detection difficult, and molecular methods necessitate costly equipment, labor, and extended sample-to-answer processing times.MethodsThis study introduces an innovative rapid DNA isolation method requiring no reagents, combined with an isothermal amplification-based assay for efficient detection of Xalb DNA in sugarcane xylem sap, leaf tissue, and meristematic tissue samples. Sugarcane samples from infected plants were subjected to heat lysis, followed by loop-mediated isothermal amplification (LAMP)-based fluorescence and colorimetric quantification within a single microcentrifuge tube.ResultsThe method exhibited exceptional detection sensitivity (detecting as low as 1 cell/μL), reproducibility [with a standard deviation (SD) of <5% for n = 3], and a broad linear dynamic range (10 pM to 1 aM or 107–100 copies/μL, r = 0.99). Quantification of Xalb was accurately correlated with sugarcane cultivar disease ratings. Validation using qPCR showed 91–98% agreement. This assay also effectively determined optimal sampling times and plant parts by monitoring the progression of the disease over time.DiscussionThis diagnostic assay holds significant potential as a commercial opportunity for a kit-based DNA extraction/purification-free molecular detection alternative. It can be adapted into a handheld device, enabling on-farm detection and quantification of the pathogen responsible for LS disease.